Development of a Social Media-Based Blended Learning Strategy for Social Studies Learning Among Elementary School Teacher Education Students - Tati Haryati; A. Gafar Hidayat; Syahbuddin, Syahbuddin (STKIP Taman Siswa Bima, 2024)
Blended learning provides a mixed learning experience for students, namely face-to-face and online. This study was designed to develop a blended learning strategy based on social media, where social media can be used as a source of additional learning information, especially in social studies courses. The objectives of this study are; 1) Describe the Development of a Blended Learning Strategy Based on Social Media in Students' Social Studies Learning; 2) Review and analyze the feasibility of a Blended Learning Strategy Based on Social Media in Students' Social Studies Learning. The research method used is research and development (R&D) to produce certain products or develop existing products. Using the ADDIE development model, through five stages; 1) Analysis; 2) Design; 3) Development; 4) Implementation; 5) Evaluation. The results of this development are in the form of guidelines or guidelines for implementing a blended learning strategy based on social media in social studies learning. Based on the results of the validation of the learning syntax expert, a value of 81.66% was obtained, with a very feasible category. While the results of student responses reached 80.33 %, with a very practical category. This means that the blended learning strategy based on social media can be used during the learning process, so that the Android device you have can access information that is in accordance with the lesson on social media